2012
DOI: 10.1097/scs.0b013e31824dbed8
|View full text |Cite
|
Sign up to set email alerts
|

New Resorbable Plate and Screw System in Pediatric Craniofacial Surgery

Abstract: Early forms of resorbable fixation induced foreign body reactions requiring surgical removal of the fixation material. Most current plating systems attempt to circumvent this phenomenon by altering the composition of the α esters involved. ResorbX (KLS Martin, Jacksonville, FL), a plating system derived from 50:50 poly(D,L)lactide, boasts short resorption times, minimal foreign body reaction, and adequate strength for bony fixation. We present our experience with 134 patients undergoing correction of primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The absence of these findings confirms the results of a recent clinical study of 129 patients described by Linz et al where stable osteosynthesis was achieved absolutely with the use of Vicryl (Ethicon, Germany) suture material. This is in contrast to numerous studies in the literature which describe similar adverse reactions from the use of absorbable plates and screws [20]. According to another clinical study performed by Sanger et al, the complication rates from the use of Vicryl sutures for osteosynthesis were under 1% [21].…”
Section: Discussionmentioning
confidence: 83%
“…The absence of these findings confirms the results of a recent clinical study of 129 patients described by Linz et al where stable osteosynthesis was achieved absolutely with the use of Vicryl (Ethicon, Germany) suture material. This is in contrast to numerous studies in the literature which describe similar adverse reactions from the use of absorbable plates and screws [20]. According to another clinical study performed by Sanger et al, the complication rates from the use of Vicryl sutures for osteosynthesis were under 1% [21].…”
Section: Discussionmentioning
confidence: 83%
“…Most common raw materials for the fabrication of biodegradable materials are polymers and copolymers of glycolicacid (polyglycolid, PGA), lactic acid (polylactid, PLA), and mixtures of D-and L-lactides (PDLLA) The biodegradation of resorbable osteosynthesis depends on 2 main factors: the composition of the material itself and the surrounding tissue. The manufactured combination determines the properties as biomechanical stability and biochemical decomposition of the osteosynthesis plates (6).…”
Section: Introductionmentioning
confidence: 99%
“…Wood et al reported on the use of ResorbX to treat 134 consecutive cases of primary craniosynostosis (20). The authors followed patients for an average of 18 months, which they suggest is the interval for complete resorption in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%